Written emotional disclosure can promote athletes` mental health and performance readiness during the COVID-19 pandemic - Davis, P. A.; Gustafsson, H.; Callow, N.; Woodman, T. (Frontiers in Psychology, 2020)
The widespread effects of the COVID-19 pandemic have negatively impacted upon many athletes` mental health and increased reports of depression as well as symptoms of anxiety. Disruptions to training and competition schedules can induce athletes` emotional distress, while concomitant government-imposed restrictions (e.g., social isolation, quarantines) reduce the availability of athletes` social and emotional support. Written Emotional Disclosure has been used extensively in a variety of settings with diverse populations as a means to promote emotional processing. The expressive writing protocol has been used to a limited extent in the context of sport, and predominantly in support of athletes` emotional processing during injury rehabilitation. We propose that Written Emotional Disclosure offers an evidence-based treatment that can promote athletes` mental health and support their return to competition. Research exploring the efficacy of the expressive writing protocol highlights a number of theoretical models underpinning the positive effects of Written Emotional Disclosure; we outline how each of these potential mechanisms can address the multidimensional complexity of the challenging circumstances arising from the COVID-19 pandemic (e.g., loss of earnings, returning to training and competition). Considerations and strategies for using Written Emotional Disclosure to support athletes during the COVID-19 pandemic are presented.